Bacterial composition in maca (Lepidium meyenii Walp) crop soils analyzed by metagenomics: a study in the central Andes of Peru - Custodio, María (2021)
The change and intensification of land use has been generating impoverishment of soils with negative effects on biological communities. It was analyzed the bacterial composition of maca (Lepidium meyenii Walp) cultivation soils by Illumina sequencing in the Bombón plateau, during 2019. Three sampling sectors were defined, a control sector (natural soil) and two sectors with use pressure ("first use" and "second use" soils). Soil physicochemical indicators were determined through analytical methods and the composition of bacterial communities through Illumina sequencing of 16S rRNA gene amplicons. The results of pH and EC, in control soils and with use pressure, varied from 7.51 to 4.53 and from 0.06 to 0.47 dS/m, respectively. The highest OM, N, P, K and Ca contents were recorded in control soils, decreasing significantly in soils with use pressure. Principal components analysis (PCA) presented a percentage of total variation of 97.1%. Illumina sequencing revealed 3776 bacterial families. SIMPER analysis showed that the highest contribution percentages were made by the Acidobacteriaceae (2.95%), Verrucomicrobiaceae (2.68%), Thermoactinomycetaceae (2.11%) and Akkermansiaceae (2.10%) families. Redundancy analysis (RDA) showed a good association between physicochemical variables and bacterial families. The metagenomic analysis has allowed the identification of bacterial families that can be used as indicators of good and bad soil physicochemical quality according to the pressure of use by maca crops. As well as the best physicochemical indicators predictive of changes in the composition of bacterial communities.